PENGARUH PADAT TEBAR YANG BERBEDA TERHADAP PENAMBAHAN JUMLAH CACING SUTRA (Tubifex sp) DENGAN SISTEM RESIRKULASI - Ike Mardiana Sari; Zulkhasyni Zulkhasyni; Dedi Pardiansyah; Suharun Martudi; Andriyeni Andriyeni (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
The purpose of this study was to determine the best stocking density for silk worms (Tubifex sp.) Against the addition of silk worms with a recirculation system. This research was conducted for 60 days starting in December 2019 until January 2020 at Jl. Bumi Ayu 8. Rt. 27 Rw. 06, Bumi Ayu Village, Selebar District, Bengkulu City. The container used is a container made of wood with a length of 100 cm, a width of 50 cm meters and a height of 15 cm as many as 16 pieces, the materials used are worm seeds, POC chicken manure, mud and soil. The design used was a completely randomized design (CRD) with 4 treatments and 4 replications so that 16 treatment units were obtained, namely: (P1) 20 gram / m2 stocking density (P2): 25 gram / m2 stocking density (P3): 30 gram stocking density / m2 (P4): stocking density of 35 grams / m2. To determine the effect of stocking density treatment on the addition of the number of individuals and the western biomass, analysis of variance was carried out at the 5% and 1% levels. Meanwhile, to determine the best stocking density, a further test of the least significant difference (LSD) was carried out at the 5% and 1% levels. The parameters observed during the study were (1) the increase in the number of individual silkworms (Tubifex sp) and (2) the total weight of silkworm biomass (Tubifex sp.) And TSS (Total Suspended Solid). The results showed that different stocking densities with the recirculation system had a very significant effect on the addition of the number of individuals, the weight gain of biomass and had a significant effect on the utilization of TSS value by silkworms (Tubifex sp) and the best increase in the number of individuals was found in stocking density (30 grams / container) with an average addition of 61,372 individuals / container and an average biomass weight of 150.074 grams / container and the best utilization of TSS values ??by silk worms (Tubifex sp.) is stocking density (30 grams / container) with an average mean TSS value 1.612 mg / L.